Maintenance model based on multi agent system improving the performance to a total quality management (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Manufacturers recognize that production systems have no value if the production equipment is unreliable. Nowadaysindustrial maintenance, strategic business function is evolving. It is inter -related to the development of knowledge and technology, the development of new business methods well as the need to reduce costs. It should not only ensure the proper functioning of equipment but also to continually improve their performance, and enhance their lives. All these factors play havoc not only the modes of organization of the maintenance function but also the activities of actors who operate in this area.